Research progress of exercise rehabilitation in patients undergoing percutaneous coronary intervention for acute myocardial infarction (急性心肌梗死患者经皮冠状动脉介入术后运动康复的研究进展) - JIA Hongwei (贾红薇); XING Zheng (邢政); DONG Yujie (董玉洁); SHAN Li (单立); LIU Yanjie (刘艳杰); WANG Jing (王晶); YI jiaxin (益嘉欣); YANG Lin (杨林) (中西医结合护理)
Exercise rehabilitation has been proven as a promising intervention for recovery of patients after percutaneous coronary intervention for acute myocardial infarction. Based on the analysis of individual’s condition, early exercise rehabilitation plan should be designed systematically and logically to reduce the mortality due to acute myocardial infarction, prevent complications, promote the early rehabilitation and improve the exercise tolerance and quality of life of the patient. This paper summarized the status quo of exercise rehabilitation and its research status, potential problems and clinical practice in patients with acute myocardial infarction after percutaneous coronary intervention, and provided reference for the establishment of exercise rehabilitation plan after percutaneous coronary intervention. (运动康复是急性心肌梗死患者经皮冠状动脉介入(PCI)术恢复行之有效的方法。早期运动康复应该基于个体的特殊状况, 有层次有逻辑设计并推进活动方案, 降低因急性心肌梗死而造成的死亡率, 规避其他症状并发, 压缩患者的治疗康复周期, 优化患者的运动耐量与生活水平。本研究针对运动康复疗法在国内外的发展、研究应用、存在的问题及其用于急性心肌梗死PCI术后的展望进行综述, 旨在为制定更完善的PCI术后运动康复方案提高可靠参考。)